A study on plant materials selection in Traditional Malay midwifery practices as potential softscape elements in Malay garden - Nooriszai Binti Ishak (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2012)
Traditional Malay midwifery practices exhibit a wide vanatlon in plant materials selection. This study established that plant materials composition selection differs greatly with respect to stage of Malay midwifery practices, locality, environmental factors and culture. A total of 13 types of Malay midwifery practices were observed in 11 different states of Malaysia from 31 traditional midwives in Kelantan, Terengganu, Pahang, Johor, Wilayah Persekutuan Kuala Lumpur, Selangor, Perak, Kedah, Perlis, N egeri Sembilan and Sarawak. Two practices were performed during prenatal treatment which is the process of lenggang perut and also prenatal diet confinement. 11 other practices were performed during postnatal treatment which can be classified into 4 categories; herbs treatment, heat treatment, massage and abstinence (pantang). The influence of plant materials composition of east coast over west coast in Malaysia or locality x culture x midwifery process x plant materials selection, in relation of creating Malay garden identity established that each factor had an effect on the composition of plant materials selection. However, the most influential factor appeared to be stage of Malay midwifery practices. Each practice has specific purposes and functions which later determine the accumulation of plant materials selection. Of all the Malay midwifery practices studied in this research we found that mandi serom is the most diverse plant species used which portray the habitat or type of environments in which these plant species origin or found. There may be similarities of some species due to similar knowledge, culture or environment; however the magnitude of these effects is not as great as plant materials composition selection and usaga. By identifying the key factors controlling plant materials selection and usage a greater understanding of how certain midwifery practices influence plant species selection and composition in response to interactions with environmental factors as well as culture, belief and taboos will emerge as potential softscape elements tools and indicator in creating identity of Malay landscape for specific culture and locality. Keywords: Malay midwifery, plant material, Malay landscape